Doctors extraordinaire - Ho, Tak Ming (Perak Academy, 2000)
An extraordinary effort by Dr Ho Tak Ming written specially about extraordinary doctors who dedicated their lives to the people and the nation. Dr Ho has done the Malaysian public a great service. He has placed on record, not in usual placid and colourless language of the serious historian but in the witty and intimate style of a writer, biographical information on certain outstanding members of the Malaysian medical profession many of whom should never be forgotten. It is particularly praiseworthy that he has dealt so lightheartedly with fact not fiction